Implementation of Fingerprint Attendance to Improve the Accuracy of Student Attendance Data - Palma Juanta; Felix; Verren A. Liandinata (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – The use of manual attendance methods in educational environments often triggers operational obstacles, ranging from recapitulation errors to loopholes for attendance manipulation by students. Consequently, the resulting data validity is low, thus hampering the effectiveness of school administration. In response to this issue, this study implemented fingerprint scanning technology to ensure the accuracy and integrity of attendance information. This research was conducted to implement a fingerprint-based attendance system as a solution to improve the accuracy and reliability of student attendance dataMethods – Data were collected through observation, interviews, and documentation at the research location. The research process included the stages of designing, implementing, and directly testing the fingerprint attendance system. Data analysis was conducted using Simple Linear Regression Testing to measure the magnitude of the effect of the fingerprint attendance system implementation on improving the accuracy of student attendance data compared to the previously used manual system Findings – Statistical data analysis proved that the use of fingerprint technology significantly affected the accuracy of attendance reports at SMA Kristen Kalam Kudus 1 Medan. Based on SPSS calculations, Y = 26.771 - 0.301X was obtained, which indicates the relationship between the independent and dependent variables in this study. Research implications – The implementation of fingerprint attendance systems can serve as an effective technological innovation for enhancing the accuracy, reliability, and transparency of student attendance data management in educational institutionsOriginality – This study offers originality by specifically examining the role of fingerprint-based attendance systems in improving the accuracy of student attendance data through empirical analysis within an educational setting, an area that has received limited attention compared to studies focusing primarily on employee attendance management.